2006
DOI: 10.1534/genetics.106.057927
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Novel Traits by Array-Assisted Bulk Segregant Analysis in Saccharomyces cerevisiae

Abstract: We demonstrate a new method, microarray-assisted bulk segregant analysis, for mapping traits in yeast by genotyping pooled segregants. We apply a probabilistic model to the progeny of a single cross and as little as two microarray hybridizations to reliably map an auxotrophic marker, a Mendelian trait, and a major-effect quantitative trait locus. M APPING the genes responsible for traits remains one of the most basic goals of genetics. There are several techniques available for reaching this goal, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 14 publications
2
78
0
Order By: Relevance
“…Complementation tests revealed that these mutants do not complement each other, implicating a single locus. One of the mutants, DBY11202, was used for both array-assisted bulk segregant analysis (14) and mutation detection by using overlapping tiling arrays of the entire yeast genome (15). The bulk segregant analysis identified one linkage peak on chromosome IV (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementation tests revealed that these mutants do not complement each other, implicating a single locus. One of the mutants, DBY11202, was used for both array-assisted bulk segregant analysis (14) and mutation detection by using overlapping tiling arrays of the entire yeast genome (15). The bulk segregant analysis identified one linkage peak on chromosome IV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Linkage analysis was performed by using a strategy described previously (14). In short, strain DBY11202 was backcrossed twice to get a 2:2 segregation (resistant; high viability upon leucine starvation, sensitive; low viability).…”
Section: Enrichment For Mutants With Enhanced Survival Upon Leucine Smentioning
confidence: 99%
“…One such method is array-assisted bulk segregant analysis (Brauer et al, 2006), which has been used to map traits in yeast. Here, yeast strains differing in genetic background and trait value are crossed.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, complex traits have been studied among strains or individuals found in nature. The advances in the efficiency of mutagenesis and whole-genome sequencing after pooled linkage analysis (Brauer et al 2006;Ehrenreich et al 2010) will allow unbiased screens in the laboratory not only for single mutations that confer traits but for the de novo creation and analysis of polygenic mutants as well. This approach opens the door for the identification and analysis of phenotypes previously unapproachable in the lab (for example: Koschwanez et al 2013).…”
mentioning
confidence: 99%